Physical activity and sport: post-COVID19 - Pérez-Turpin, J. A.; Gomis-Gomis, M. J. (Journal of Human Sport & Exercise, 2020)
With the horizon of a new normal around the corner, physical activity and sport have proven to be one of the best weapons to combat this period of forced confinement, which has left a new stage of health, physical activity, and sports, where these four signs of identity that are here to stay receive more value than ever: 1.-) Health care through motor skills 2.-) Protecting the environment starting on sports practic. 3.-) Technological advances in physical activity and sport are here to stay. 4.-) Scientific knowledge as the only way of physical activity and sport